TEACHING WRITING AND ITS STAGES - Gaforov Iqboljon Uktamovich; Saodatxon Abdullayeva Nozimjon qizi; Avvalbekova Dildora Hoshimjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Writing is the most complicated skill of the four language capabilities which are reading, speaking, comprehension and listening. Writing integrates almost all the different three elements. Given the fact of our tremendously dynamic and interconnected world, to be able to write efficiently and exactly is a necessary competence that need to be aimed at. This makes teaching writing a giant activity. This annotation offers a concise overview of teaching writing strategies and stages of writing process.